PENGARUH PENGUASAAN BAHASA ARAB TERHADAP KEMAMPUAN MENGHAFAL AL-QUR’AN MAHASISWI SEMESTER II MA’HAD AL-BIRR MAKASSAR - Nur Siah; Nur Fadilah Amin (Universitas Muhammadiyah Makassar, 2017)
Language is the means of communication in sharing thoughts, ideas, concepts or feelings used by humans both orally and writing. Every nation has its own language, for example Arabic . Arabic is the language that used by the Arabian society. It has a distinctive as the language that is used in the Qur'an, the holy book of Moslem . Arabic Language then became one of the language that is studied all over the world. There are Some opinions that learning Arabic is one of the most difficult and hard to do, so that some people still not interested to learn it. But Without conscious, by studying Arabic and understanding it well, it will be very helpful in memorizing and mastering the Holy Qur'an. This research was conducted at Ma'had Al-Birr Makassar in Jl.Sultan Alauddin 259 Makassar . This study aims To determine the influence of mastery the Arabic language and the ability to memorize Al-Qur'an of the second semester student on Ma'had Al-Birr Makassar. This research is expected to gives good benefit For Students to improve their motivation in memorizing and mastering Al-Qu'ran, for the lecturers are expected can help to provide learning motivation student in mastery and memorize Al-Qu'ran. Besides, for the researchers are expected to provide benefits to apply and implement Arabic language in memorize Al-Qur'an. The research method used is a quantitative approach such as Interview Guide, questionaires, Observation Guide and files. The data obtained was analyzed by regression analysis and Anova 5% (percent). The result of this research is the ability of mastery of Arabic language by second semester student on Ma